Sharing the space: Seven livestock leaders speak out on a global agenda - International Livestock Research Institute (International Livestock Research Institute, 2012)
What are future directions for the livestock sector — particularly its potential to help alleviate world poverty and hunger without harming human health and the environment? Here, seven leaders in livestock development thinking reflect on the outcomes of a ’High-Level Consultation for a Global Livestock Agenda to 2020′ (12–15 March 2012) co-hosted by the World Bank and the International Livestock Research Institute (ILRI) and held at ILRI’s headquarters, in Nairobi, Kenya. The seven participants interviewed are (1) Francois Le Gall, co-host of this consultation and livestock advisor at the World Bank; (2) Henning Steinfeld, chief of livestock information and policy at the United Nations Food and Agriculture Organization (FAO); (3) Kristin Girvetz, program officer at the Bill & Melinda Gates Foundation; (4) Bernard Vallat, director general of the World Organisation for Animal Health (OIE); (5) Boni Moyo, ILRI representative for southern Africa; (6) Carlos Seré, chief development strategist at the International Fund for Agricultural Development (IFAD); and (7) Jimmy Smith, co-host of this event and director general of ILRI.